1997
DOI: 10.4141/s96-022
|View full text |Cite
|
Sign up to set email alerts
|

Sulphate sorption in relation to properties of podzolic and brunisolic soils in northeastern Ontario

Abstract: Sulphate sorption in relation to properties of podzolic and brunisolic soils in northeastern Ontario. Can. J. Soil Sci. 77: 397-404. An insight into sulphate (SO 4 2-) retention by podzolic and brunisolic soils was obtained by examining SO 4 2-sorption by B horizons from forest soils in northeastern Ontario. The amount of water soluble and adsorbed SO 4 2-present in the soils and the ability to adsorb additional SO 4 2-was evaluated. Relationships between soil pH, organic carbon and different iron (Fe) and alu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…[44] In contrast to ultisols, retention of sulfate was positively correlated with inorganic amorphous Al in podzolic soils. [45] According to current results, the average total amounts of S declined with depth of soil following same pattern as average total carbon in all soil series. Our results are in agreement with those of Möller et al [46] who presented that status of S in tropical soils depended closely on the turnover rate and content of organic matter.…”
Section: Principal Component Analysis Of Sulfursupporting
confidence: 64%
“…[44] In contrast to ultisols, retention of sulfate was positively correlated with inorganic amorphous Al in podzolic soils. [45] According to current results, the average total amounts of S declined with depth of soil following same pattern as average total carbon in all soil series. Our results are in agreement with those of Möller et al [46] who presented that status of S in tropical soils depended closely on the turnover rate and content of organic matter.…”
Section: Principal Component Analysis Of Sulfursupporting
confidence: 64%
“…, Bhatti et al. ). Concentrations of Al and Fe oxide are thus proxies of the amounts of inorganic P and S potentially available in soils.…”
Section: Discussionmentioning
confidence: 99%
“…The close association observed between SO 4 n and Si o at PGJ is less common and poorly documented in studies relating SO 4 sorption to soil properties. For example, Bhatti et al (1997) found no relationship between various SO 4 sorption indices and Sio in 55 Podzols from Canada. However, significant SO 4 -Sio correlations were observed in 33 forest soils from Scandinavia and in 23 Canadian Brunisols (Gustaffson et al 1995;Bhatti et al 1997).…”
Section: So 4 Retentionmentioning
confidence: 96%
“…For example, Bhatti et al (1997) found no relationship between various SO 4 sorption indices and Sio in 55 Podzols from Canada. However, significant SO 4 -Sio correlations were observed in 33 forest soils from Scandinavia and in 23 Canadian Brunisols (Gustaffson et al 1995;Bhatti et al 1997). The association between Sio and SO 4 sorption suggests that the surfaces of short-range ordered aluminosilicates contribute significantly to total positively charged sites, and thus to anion retention, in OM-poor B horizons.…”
Section: So 4 Retentionmentioning
confidence: 96%